Enteral feeding regimens and necrotising enterocolitis in preterm infants: a multicentre case–control study. Issue 2 (3rd September 2007) - Henderson, G; Craig, S; Brocklehurst, P; McGuire, W
Abstract : Background: Most preterm infants who develop necrotising enterocolitis (NEC) have received enteral feeds. Uncertainty exists about which aspects of the feeding regimen affect the risk of NEC. Aim: To examine associations between various enteral feeding practices and the development of NEC in preterm infants. Methods: Multicentre case–control study. 53 preterm infants with NEC were enrolled together with a gestational age frequency-matched control without NEC from a randomly selected neonatal unit. Clinical and feeding data were extracted and compared between the groups. Results: Significantly fewer cases than controls had received human breast milk (75% vs 91%; OR 0.32, 95% CI 0.11 to 0.98). The day on which enteral feeding was started did not differ significantly (mean (SD) days after birth: cases 2.9 (2.8) and controls 2.8 (1.8)). The mean (SD) duration of trophic feeding (<1 ml/kg/h) was significantly shorter in the cases (3.3 (3.1) days) than controls (6.2 (6.7) days) (mean difference (MD) −2.9, 95% CI −4.9 to −0.9) days. Cases were fully fed significantly earlier than controls (mean (SD) days after birth: cases 9.9 (4.2) and controls 14.3 (9.8); MD −4.4, 95% CI −7.3 to −1.5). Conclusions: These data suggest that the duration of trophic feeding and rate of advancement of feed volumes may be modifiable risk factors for NEC in preterm infants. Further randomised controlled trials are warranted to assess the effect of different rates of feed advancement on the incidence of NEC, as well as other outcomes.